Financial risk management system at the enterprise. (Journal of Economic Research & Business Administration, 2016)
Problems of financial risk management in the enterprise in conditions of open currency position and Kazakhstan national currency weakening processes are considered. The relevance of financial risk management and improvement of financial risk management system of Kazakhstan enterprises are shown. The definition of risk management is given, financial risk management process of the enterprise is described. Characteristics of main types of financial risks of enterprises is considered. The evaluation of acting unprofitable enterprises in Kazakhstan is given. Methods of financial risk management are considered, and out of them forecasting and planning methods, and also insurance methods are emphasized. The results of the monitoring of enterprises-representatives of main Kazakhstan economy’s sectors and share of enterprises suffered from negative currency rates changes are worked out. The conclusion of practicability of integrated risk management systems in companies is enunciated.
Keywords: financial risk; financial risk management system; risk management; methods of evaluation of financial risks; risk management techniques; the method of planning and forecasting; insurance.